Members of his body: Shakespeare, Paul, and a theology of nonmonogamy - Stockton, William (Fordham University Press, 2017)
Framing the Christian defense of marital monogamy against Ephesians 5's suggestion that all believers are married in Christ, this book argues for the presence of competing marriage theologies in four Shakespeare plays: The Comedy of Errors, The Merchant of Venice, Othello, and The Winter's Tale